2019
DOI: 10.22369/issn.2153-4136/10/1/13
|View full text |Cite
|
Sign up to set email alerts
|

Using Virtual Reality to Enforce Principles of Cybersecurity

Abstract: The Cyberinfrastructure Security Education for Professionals and Students (CiSE-ProS) virtual reality environment is an exploratory project that uses engaging approaches to evaluate the impact of learning environments produced by augmented reality (AR) and virtual reality (VR) technologies for teaching cybersecurity concepts. The program is steeped in well-reviewed pedagogy; the refinement of the educational methods based on constant assessment is a critical factor that has contributed to its success. In its c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…When compared to earlier results, this proposed approach tends to perform better in measurement criteria particularly in terms of presence, control, active learning as well as reflective thinking -all these factors significantly affect learning outcomes. Seo and his colleagues in [30] explored the impact of using VR learning environments for teaching cybersecurity concepts. Simple evaluation using observation and feedback suggested that students' short and long term memory can benefit in engaging manner.…”
Section: Introductionmentioning
confidence: 99%
“…When compared to earlier results, this proposed approach tends to perform better in measurement criteria particularly in terms of presence, control, active learning as well as reflective thinking -all these factors significantly affect learning outcomes. Seo and his colleagues in [30] explored the impact of using VR learning environments for teaching cybersecurity concepts. Simple evaluation using observation and feedback suggested that students' short and long term memory can benefit in engaging manner.…”
Section: Introductionmentioning
confidence: 99%
“…Seo ve arkadaşları, Profesyoneller ve Öğrenciler için Siber Altyapı Güvenliği (CiSE-ProS) adını verdikleri ve siber güvenlik içeriklerini öğretmek amacıyla sanal gerçeklik ve artırılmış gerçeklik (AR) teknolojileri kullanılarak geliştirilmiş öğretim ortamlarının etkisini uzmanlar ve öğrenciler açısından değerlendiren bir araştırma projesi geliştirmişlerdir. [19]. Yapılan çalışmada CiSE-ProS uygulamasında eğitim alan lisans öğrencilerine kısa ve uzun vadeli öğrenme konusunda fayda sağladığı belirtilmiştir.…”
Section: Literatür çAlışmasıunclassified
“…However, the given principles are outdated, based on the modern development of innovative computer and communication technologies, and theyneed to be clarified. Thus, Jinsil Seo and others explained the impact of modern information processing technologies (including virtual reality technologies) on the transformation of the principles of cybersecurity of enterprises [7]. A similar view is given by Raj Badhwar on the need to revise conservative principles of cybersecurity in conditions of implementation of artificial intelligence technologies [8].…”
Section: качество учетной информации и принципы ее киберзащитыmentioning
confidence: 99%